Modelamiento Del Proceso De Embutición Utilizando El Método De Elementos Finitos - Rabines Caballero, Carlos Gianfranco (2018)
The present work entitled "Modeling the Embedding Process Using the Finite Element Method". This study aims to obtain a methodology and a simple sequence that leads to a rapid and consistent formulation in such a way that a computer simulation can be carried out. Determining what types of considerations should be taken into account to formulate a simulation approach in the sausage, establishing the relevant methodology that guides us throughout the modeling process, making the most appropriate formulation, choosing the most appropriate elements, and determining the distribution and behavior of the mechanical parameters during the sausage process. In such a way that they can increase their level of capacity, performance of the process, as well as greatly reduce the sausage tests since we would know with much more accuracy what could happen during the sausage and if any problem arises we will avoid the cost by trials of construction of previous matrices. For this simulation SAE 1020 was used as a material that has been studied extensively and we have values in bibliography that agree with the values found, as well as the stress distribution as expected in the theoretical distribution of voltages. Unfortunately, when using other materials we faced that we needed other data mainly in relation to the plastic behavior that prevented us from carrying out situations that were not the material mentioned above. At the conclusion of this work we wanted to have implemented a code but the programming and many problems to try to run the code made us desist from this task, a tour and an explanation of the methodology to be followed, showing the theoretical and operative part referring to a software. specifically, in addition all the considerations that the problem presents to know how to choose properly any of the presented procedures were established, an exposition was made of which formulations are the most appropriate for the sausage. All the elements (Shell) that could be used in reference to the specific software were explained.